A Work study on Company X (a printing press) - Aguirre, Ian Jason; Cruz, Redentor; Primicas, Jose Jesus; Remigid, Reubenllexo; Tiu, Luther (College of Engineering, 1993)
With the onset of technology, most firms are faced with the problem of maximizing its resources. As time progresses, every company must be able to optimize its meager resources if it hopes to stay alive in the business world. The fulfillment of a work study for a company would prove to be very beneficial as it may be translated as taking the first step towards maximization of resources. Company X, like any other company, has a lot of room for improvement. The absence of time standards, the inclusion of too many steps in their processes, and the utilization of too many forms are just some of the points which could be done away with. The elimination of these unnecessary factors in their processes, plus the establishment of standards regarding processes and operations in their production would eliminate any misunderstanding that would arise in the flow of operations. In addition to this, elimination of unwanted time elements or unnecessary time would be very likely with the implementation of the standards developed through the work study undertaken. In terms of cost benefits, the company would realize the extent of advantages such as this said project. Considering that the company makes use of automation in most of its operations, any improvements would result to the improvement itself multiplied by the repetitions involved in the processes. Elimination of excess time over standard time could free personnel and utilize their time to other productive uses, not to mention being able to finish if not on time, ahead of schedule. To close, the group would like to reiterate the importance of a project such as the work study. It not only provides management with the information regarding processes undertaken in the production area but also it gives them a general overview of the company and how to streamline their operations. In optimizing their resources, the company would have the advantage of better utilization of their invested capital.